The validation and application of a new learning environment instrument to evaluate online learning in higher education - Chang, Vanessa; Fisher, Darrell (Australian Association for Research in Education, 2001)
More and more academics are accepting the challenge of using the web-based or on-line learning in higher education to deliver coursework. Many web sites indicate that opportunities for students to receive coursework via the web is routine at most universities. The Internet/Web has become an important change agent in higher education and universities are reviewing their strategic plans to incorporate on-line learning. As a result of the increase in on-line courses, it is timely for learning environment research to focus on the Web. However, to date, no comprehensive instruments have been developed to assess on-line learning environments for higher education. A new web-based learning environment instrument is described in this paper. The Web-based Learning Environment Instrument (WEBLEI) contains four main scales. Three scales (emancipatory, co-participatory, and qualia) are built upon the work of Tobin (1998). The other scale focuses on information structure and the design of on-line material. The rationale behind, and development of, the WEBLEI are described in the paper. Statistical analyses, Cronbach alpha reliability coefficient, factor analysis, and discriminant validity, indicated that the WEBLEI is a reliable and valid instrument. The paper also reports on findings involving the perceptions of undergraduate and graduate students utilising this new instrument.